1992
DOI: 10.1381/096089292765560411
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up of Gastroplasty in a Patient with Prader-Willi Syndrome

Abstract: To prevent the development of metabolic disturbances caused by overeating, we performed vertical banded gastroplasty in an adult woman with Prader-Willi syndrome. Her fasting blood sugar (FBS) and urinary sugar excretion (US) decreased during 6 months after the surgery under strict dietary control in the hospital. The insulin response to oral glucose at 6 months after surgery was as good as in the normal controls. A barium meal study in the 11th postoperative month revealed that the staple line was partially r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…Yet, in these patients, a drastic body weight reduction is mandatory to reduce the risk of cardio-respiratory and metabolic complications and to improve life expectancy. In the last three decades, several bariatric surgical techniques were applied to treat morbid obesity in PWS patients, such as trunkal vagotomy [13], jejunoileal bypass [14,15], vertical banded gastroplasty [16,17], adjustable silicon gastric banding [18], gastric bypass [19], and biliopancreatic diversion (BPD) [20][21][22][23][24][25][26]. However, a higher morbidity and mortality rate in these patients, compared to those with simple obesity, has been reported [27].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, in these patients, a drastic body weight reduction is mandatory to reduce the risk of cardio-respiratory and metabolic complications and to improve life expectancy. In the last three decades, several bariatric surgical techniques were applied to treat morbid obesity in PWS patients, such as trunkal vagotomy [13], jejunoileal bypass [14,15], vertical banded gastroplasty [16,17], adjustable silicon gastric banding [18], gastric bypass [19], and biliopancreatic diversion (BPD) [20][21][22][23][24][25][26]. However, a higher morbidity and mortality rate in these patients, compared to those with simple obesity, has been reported [27].…”
Section: Discussionmentioning
confidence: 99%
“…A gastroplastia vertical foi realizada em uma paciente com SPW, tendo ocorrido ruptura parcial da linha de grampeamento no 11 o mês pós-operatório (50). O comportamento alimentar da paciente pode ter sido a causa para a falência da gastroplastia.…”
Section: Tratamento Cirúrgicounclassified
“…Table 3, 42 patients (including our case) with PWS-associated obesity treated with bariatric surgery were found in the English literature. Several surgical techniques have been reported on the matter, such as trunkal vagotomy [17], jejunoileal bypass [13,18,19], vertical banded gastroplasty (VBG) [20,21], adjustable silicon gastric banding [22], gastric bypass [23,24], and BPD [14,15,[25][26][27]. However, the optimal procedure is far from settled.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric restrictive operations, VBG [20,21], and adjustive silicon gastric banding (ASGB) [22], despite their initial encouraging results, failed to maintain long-term weight loss [20,21], probably because of the poor patient compliance after the intervention. Mason et al [21] reported 2 patients with PWS-associated obesity treated with VBG.…”
Section: As Shown Inmentioning
confidence: 99%
See 1 more Smart Citation